The construction of the Malaysian Educators Selection Inventory (MEdSI): a large scale assessment initiative - Othman, Joharry; Borhan, Lihanna; Abdullah, Nabilah; Wan Jaafar, Wan Marzuki; Mohd Noah, Sidek; Ahmad, Jamaludin; Sulaiman, Tajularipin; Abdul Karim, Abdul Malek; Ibrahim, Sapon; Ab. Hadi, Mohd Yusop; Abdul Rahman, Abdul Malik; Syed Mansor, Syed Mohamed Shafeq; et al. (Asian Centre for Research on University Learning and Teaching (ACRULeT), Faculty of Education, Universiti Teknologi MARA, 2008)
The crucial role that teachers and schools play in the development of a nation’s human resource is undeniable. In Malaysia, teaching has always been perceived as a financially secure and relatively easy job by many, resulting in mass application for entry into teacher education programmes. Many of those who aspire and opto to go into the teaching profession however do so regardless of their personal interests, potential, and values. Pursuing a program that does not fit a person’s personality and interest – despite initially having good academic credentials and excellent co-curricular involvement in school – may result in unsatisfactory academic performance, frustration, change of program and even withdrawal at college level. Hence, in the quest for selecting suitable teacher trainee candidates, a psychometrically sound instrument known as the Malaysian Educators Selection Inventory (MEdSI) was developed as a screening measure to filter the large number of teacher hopefuls. This paper specifically describes the theoretical basis and the constructs of the instrument developed.